Microfluidic Flow Injection Immunoassay System for Algal Toxins Determination: A Case of Study - Celio, Lorenzo; Ottaviani, Matteo; Cancelliere, Rocco; Di Tinno, Alessio; Panjan, Peter; Sesay, Adama Marie; Micheli, Laura (Frontiers in Chemistry, 2021)
A novel flow injection microfluidic immunoassay system for continuous monitoring of saxitoxin, a lethal biotoxin, in seawater samples is presented in this paper. The system consists of a pre-immobilized G protein immunoaffinity column connected in line with a lab-on chip set-up. The detection of saxitoxin in seawater was carried out in two steps: an off-line incubation step (competition reaction) performed between the analyte of interest (saxitoxin or Ag, as standard or seawater sample) and a tracer (enzyme-conjugated antigen or Ag*) toward a specific polyclonal antibody. The mixture was, then, injected through a "loop" of a few μL using a six-way injection valve into a bioreactor, in line with the valve. The bioreactor consisted of a small glass column, manually filled with resin upon which G protein has been immobilized. When the mixture flowed through the bioreactor, all the antibody-antigen complex, formed during the competition step, is retained by the G protein. The tracer molecules that does not interact with the capture antibody and protein G is eluted out of the column, collected and mixed with an enzymatic substrate directly within the microfluidic chip, via the use of two peristaltic pumps. When Ag* was present, a colour change (absorbance variation, ΔAbs) of the solution is detected at fixed wavelength (655 nm) by an optical chip docking system and registered by computer. The amount of saxitoxin, present in the sample (or standard), that generate the variation of the intensity of the colour, will be directly proportional to the concentration of the analyte in the analysed solution. Indeed, the absorbance response increased proportionally to the enzymatic product and to the concentration of saxitoxin in the range of 3.5x10-7 – 2x10-5 ng mL-1 with a detection limit of 1x10-7 ng mL-1 (RSD% 15, S N-1 equal to 3). The immunoanalytical system has been characterised, optimized, and tested with seawater samples. This analytical approach, combined with the transportable and small-sized instrumentation, allow for easy in situ monitoring of marine water contaminations.